Rebranding the Visual Identity of +62 Voice: A Human-Centered Design Approach for a Roblox-Based Community - Natasya Safarani Riady; Anung Rachman (Institut Seni Indonesia Yogyakarta, 2025)
This project focuses on the redesign of the visual identity of +62 Voice, a voice chat-based community on Roblox. Previously, the community relied on AI-generated visuals that were generic and failed to reflect the emotional and social character of the group. Through a human-centered design approach and Design Thinking methodology, the project aimed to create a cohesive, contextual, and meaningful visual identity aligned with the values of the community. Qualitative research was conducted through interviews and questionnaires involving the owner, admins, and developers. The design process was iterative and participatory, involving the creation of a logo, icons, illustrations, and social media content—all developed in response to community feedback. Key visual elements such as the microphone symbol, bright color palette, and personalized avatar illustrations were used to build a narrative that visually represented the voice-chat function and collective identity. The results showed strong positive responses from the community. The new visuals were considered more lively, consistent, and representative than previous AI-generated designs. These findings reinforce the vital role of human designers in producing meaningful, context-aware branding that surpasses AI efficiency.